Karakteristik temuan radiologis pada pasien low back pain di RSUP Sanglah Denpasar periode Maret 2016-Oktober 2017 - Komang Mila Triana Sari; Elysanti Dwi Martadiani; Made Widhi Asih (Intisari Sains Medis, 2019)
Background: Low back pain (LBP) is a common problem in almost all parts of the world. It may cause disability and a huge social and economic burden in the community. Radiological examination is often necessary to help the doctor in evaluating LBP.Aim: The study aims to find out the radiological characteristics of LBP as a preventive effort against those case.Method: The study was descriptive cross-sectional design involved 65 LBP patients as study respondents in Sanglah General Hospital from March 2016-October 2017.Result: Characteristics of LBP patients are male patients and patients aged 50-59 years. Both are the most frequent sample which were found out in the study.Conclusion: The most common radiological findings in each examination modality are as follows: osteophytes on Radiographic examination, burst fracture, compression fracture and fractures of spinous process on CT scan, and spinal canal stenosis on MRI examination.